2021
DOI: 10.3389/fonc.2021.752604
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin Ligases in Breast Cancer Metastasis: A Systematic Review of Pathogenic Functions and Clinical Implications

Abstract: Female breast cancer has become the most commonly occurring cancer worldwide. Although it has a good prognosis under early diagnosis and appropriate treatment, breast cancer metastasis drastically causes mortality. The process of metastasis, which includes cell epithelial–mesenchymal transition, invasion, migration, and colonization, is a multistep cascade of molecular events directed by gene mutations and altered protein expressions. Ubiquitin modification of proteins plays a common role in most of the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 138 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Although median levels of bTMB and bCNB were not significantly increased at the time of clinical progression relative to baseline, we observed enrichment of individual alterations previously implicated in endocrine and/or CDK4/6i treatment resistance including AR, AURKA, CCND1, CDKN2A, ESR1, FGFR1, MYC and RB1 (47). We also observed enrichment of alterations in genes less commonly associated with ET and CDK4/6i treatment resistance, which encode a variety of oncogenic proteins, including CBL, a member of the RING finger ubiquitin ligase family that regulates receptor tyrosine kinase signaling (56)(57)(58); KMT2D, a methyltransferase involved in estrogen receptor recruitment and activation (59); MUC12, a glycosylated transmembrane protein in the mucin family implicated in the regulation of proliferation, invasion and metastatic potential (60)(61)(62); and PREX2, a guanine nucleotide exchange factor that regulates cancer cell motility and invasion (63,64). Many of these novel alterations are not covered by targeted sequencing panels, underscoring the value of the extended WES to identify diverse mechanisms of resistance.…”
Section: Discussionmentioning
confidence: 67%
“…Although median levels of bTMB and bCNB were not significantly increased at the time of clinical progression relative to baseline, we observed enrichment of individual alterations previously implicated in endocrine and/or CDK4/6i treatment resistance including AR, AURKA, CCND1, CDKN2A, ESR1, FGFR1, MYC and RB1 (47). We also observed enrichment of alterations in genes less commonly associated with ET and CDK4/6i treatment resistance, which encode a variety of oncogenic proteins, including CBL, a member of the RING finger ubiquitin ligase family that regulates receptor tyrosine kinase signaling (56)(57)(58); KMT2D, a methyltransferase involved in estrogen receptor recruitment and activation (59); MUC12, a glycosylated transmembrane protein in the mucin family implicated in the regulation of proliferation, invasion and metastatic potential (60)(61)(62); and PREX2, a guanine nucleotide exchange factor that regulates cancer cell motility and invasion (63,64). Many of these novel alterations are not covered by targeted sequencing panels, underscoring the value of the extended WES to identify diverse mechanisms of resistance.…”
Section: Discussionmentioning
confidence: 67%
“…Different types of post-translational modifications (PTMs) of proteins are associated with different types of cancer. Some studies reported that the phosphorylation, succinylation, and ubiquitination sites of proteins are the BC-causing PTM sites [110,[112][113][114]. Therefore, we verified the resistance power of the top-ranked three ligands (Suramin, Rifaximin, and Telmisartan) against the phosphorylation, succinylation, and ubiquitination sites of BC-causing HubGs-mediated receptor proteins by molecular docking analysis.…”
Section: Hubgs-guided Drug Screening By Molecular Dockingmentioning
confidence: 77%
“…RING finger (RNF) proteins comprise a large family of proteins which play pivotal roles in protein ubiquitination. Ubiquitination is mainly involved in mediating protein degradation, which in turn regulates cellular activities [ 8 , 9 ]. It has been reported that ubiquitination participates in lots of intracellular biological processes, such as affecting DNA damage repair, modulating cell metabolism, regulating cell death, and altering therapeutic effect [ 10 ].…”
Section: Introductionmentioning
confidence: 99%